Social Message On #Cari_Aman Safety Riding Video : Semiotics study - Zhafran Fatih Ananda; Ikhwanuddin Nasution; Rohanie Ganie (East Asian Journal of Multidisciplinary Research, 2022)
The objective of the research was to find the types of signs, to identify denotation, connotation, and myth, and to analyze the underlying social messages in the safety ride advertisement on the #cari_aman safety riding video. The research data used verbal and visual data sourced from youtube platform tagged #cari_aman which is safety riding campaign advertisement of the motorcycle manufacture named Honda. The research employs a descriptive qualitative method by adopting an interactive model and qualitative data analysis procedure proposed by Miles and Huberman. The data analysis used the theory of sign perspective in semiotics by Pierce and semiotic perspective by Barthes. The results show that the types of signs in semiotics which are used in the data are icon (63%) which is the most dominant one, index (22%) and symbol (13%). The denotation is manifested by interpreting the situation in the research data with subjective feelings or emotions and the meaning of myth is manifested by conceptualizing or understanding the research data into the culture that develops in society. The research finds that the underlying social meaning is delivered by containing the events close to young people’s daily life using kinesic meaning through body movement; proxemics meaning through adjusting distance and space; artifactual meaning through body image; and paralinguistic through pronunciation way of verbal message.